The consequences of doing nothing inaction insertia as avoidance of anticipated counterfactual regret - Tykocinski, Orit E.; Pittman, Thane S. (American Psychological Association Inc., 1998)
When an attractive action opportunity has been forgone, individuals tend to decline a substantially less attractive current opportunity in the same action domain, even though, in an absolute sense, it still has positive value. The hypothesis that continued inaction (inaction inertia) occurs in the service of avoiding anticipated regret was tested. In Experiments 1 and 2, when repeated contact with the forgone opportunity (and, hence, the experience of regret) was made unavoidable, the tendency toward subsequent inaction decreased. The inaction inertia effect was also reduced when avoidance costs were increased (Experiment 3) or when the initial reason for avoidance was removed (Experiment 4). Experiment 4 included a thought-listing task that provided direct evidence for the role of regret in producing inaction inertia.